A presença do Prólogo do Quarto Evangelho no gnosticismo alexandrino do século II - Dutra, Rafael Antonio Faraone (2018)
The similarity of John writings and the gnostics is still a lasting subject nowadays. All discoveries that attempt to clear things up get people’s attention. The discoveries of Nag Hammadi writings, whose some texts are gnostics, points at an Alexandrian II century AD Gnosticism that suffered from various influences, mostly Johannine. The exploration of such environment allow us not only to notice John richness, but also his diffusion in religious environments. Some of the writings of Nag Hammadi, as Trimorfaic Protenor, John Apocryphal and Gospel of Truth, have vocabularies and thematic affinities with the Fourth Gospel, especially with the Prologue. Through the similarity with the quoted texts, the question arises whether the texts of Alexandrian II century AD were used from John prologue to his composition. The hypothesis is that somehow the Gnostics had contact with the Johannine prologue and used their concepts to base their teachings. In order to answer this question, this work has bibliographic character, using the literature concerning the prologue of the Fourth Gospel and the analysis of the quoted texts and the prologue, from the tradition and the contemporary exegesis